Analisis Potensi Wisata Kebudayaan Berbasis Kewirausahaan Sosial Seni Badeng Kasepuhan Mandalawangi - Lidinil Islami, Nurul Azmi; Mustopa, Moh Ripqi; Azahra, Sevina; Laskono, Bayu Adi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Abstract. The potential of culture and local wisdom in tourism development is part of the product of human creativity that has economic value of human creativity that has economic value. The purpose of the study was to analyze the potential of cultural tourism based on social entrepreneurship in seni Badeng kasepuhan Mandalawangi. The research method used is qualitative analysis through direct observation and indepth interviews with relevant parties. While the analysis method used is Sternght, Weakness, Opportunity and Threats (SWOT) analysis. Strenght, Weakness, Opportunity, and Threat (SWOT) analysis is used to analyze the potential and problems in culture-based tourism and local wisdom at the research location including internal and external potential and problems. Local culture, especially in Tanjungmekar Village, Jamanis Subdistrict, Tasikmalaya Regency in general, has unique potential in seni Badeng that can be developed to improve local cultural tourism. The strategy for increasing local cultural tourism is formulated based on the strengths, weaknesses, opportunities and threats of local culture. With this research, the existence of Badeng art can be used as an introduction to local cultural tourist destinations (DTW).